2002
DOI: 10.1074/jbc.m206569200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mutation (T65P) in the PAS Domain of the Human Potassium Channel HERG Results in the Long QT Syndrome by Trafficking Deficiency

Abstract: The congenital long QT syndrome is a cardiac disease characterized by an increased susceptibility to ventricular arrhythmias. The clinical hallmark is a prolongation of the QT interval, which reflects a delay in repolarization caused by mutations in cardiac ion channel genes. Mutations in the HERG (human ether-à -go-go-related gene KCNH2 can cause a reduction in I Kr , one of the currents responsible for cardiac repolarization. We describe the identification and characterization of a novel missense mutation T6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 40 publications
5
90
1
Order By: Relevance
“…Our data with hERG C66G and L86R are different from previous reports from oocytes that showed robust currents (14). The most likely explanation for differences in channel expression between oocytes (previous study) and HEK293 cells (this study) is a temperature-sensitive folding defect that is apparent with differences in culture temperature for oocytes (16°C) versus HEK293 cells (37°C), as described for other hERG LQT2 mutant channels (16,20,21,29).…”
Section: Discussioncontrasting
confidence: 56%
“…Our data with hERG C66G and L86R are different from previous reports from oocytes that showed robust currents (14). The most likely explanation for differences in channel expression between oocytes (previous study) and HEK293 cells (this study) is a temperature-sensitive folding defect that is apparent with differences in culture temperature for oocytes (16°C) versus HEK293 cells (37°C), as described for other hERG LQT2 mutant channels (16,20,21,29).…”
Section: Discussioncontrasting
confidence: 56%
“…Is this a unique feature of CNBD or will other highly structured domains have similar effects? It has been recently shown that a mutation in the PAS domain causes ER retention (Paulussen et al, 2002). However, it has also been reported that other mutations in the PAS domain or N-terminal truncations that eliminate this domain do not always preclude generation of functional HERG channels (Morais Cabral et al, 1998;Chen et al, 1999;Wang et al, 1998;Viloria et al, 2000;Gomez-Varela et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…WT-hERG mainly labelled at the surface membrane ( Figure 2A); in contrast, the trafficking-defective G572R-hERG was mainly expressed in the cytoplasm ( Figure 2C) (20,21). Figure 2B shows that G572R-hERG/WT-hERG results in less plasma membrane fluorescence compared with the consequences of WT-hERG.…”
Section: Western Blotting and Immunocytochemistry Analysesmentioning
confidence: 99%